Optical properties of GaAs/AlxGa1-xAs/GaAs quantum dot with off-central impurity driven by electric field - Holovatsky, V.A.; Yakhnevych, M.Ya.; Voitsekhivska, O.M. (Condensed Matter Physics, 2018)
The effect of a constant electric field and donor impurity on the energies and oscillator strengths of electron intraband quantum transitions in double-well spherical quantum dot GaAs/AlxGa1−xAs/GaAs is researched. The problem is solved in the framework of the effective mass approximation and rectangular potential wells and barriers model using the method of wave function expansion over a complete set of electron wave functions in nanostructure without electric field. It is shown that under the effect of electric field, the electron in the ground state tunnels from the inner potential well into the outer one. It also influences on the oscillator strengths of intraband quantum transition. The binding energy of an electron with ion impurity is obtained as a function of electric field intensity at a different location of impurity.